Changes in home range sizes and population densities of carnivore species along the natural to urban habitat gradient. (25th September 2014) - Šálek, Martin; Drahníková, Lucie; Tkadlec, Emil
Abstract With rapid development and the spread of urbanized land, there is an increasing need to understand species' responses to urban conditions. Carnivores are considered to be sensitive to urbanization; however, there is ample evidence that some carnivore species successfully inhabit urban areas, and human‐modified habitats have recently been recognized as an important refuge for several species. Despite the increasing number of studies on urban carnivore ecology, no comprehensive cross‐species comparisons have been made in order to assess the effects of urbanization on the spatial ecology of carnivores and their population densities. Such a review could provide interesting insight into how some carnivore species respond to increasing urbanization. Specifically, we examine changes in population density and home range size of eight carnivore species that occur along the natural–urban environmental gradient. Using data from 411 articles, we provide evidence that the home range size of carnivores decreases in six out of eight species, and population density increases in three out of six species along the natural–urban habitat gradient. The density‐dependent pattern of variation in home range size is consistent in all species studied. Our results emphasize the remarkable ability of some carnivore species to adapt to novel environments through their behavioural flexibility and life history adaptations. We outline ideas for future research that could be adopted in addressing this phenomenon, namely comparative approaches and detailed studies of biotic and abiotic conditions along natural–urban gradients.